2015
DOI: 10.1590/1089-6891v16i430548
|View full text |Cite
|
Sign up to set email alerts
|

Redução Do Tempo No Processo De Cozimento De Mortadela E Avaliação Da Qualidade Final Do Produto

Abstract: Resumo Em indústrias de alimentos, o processo de cozimento é um dos mais importantes para a conservação e garantia da qualidade do produto final, principalmente de mortadelas. Porém, este é um processo que necessita de elevados investimentos em equipamentos modernos, além de apresentarem gastos com energia elétrica e vapor. Neste contexto, o objetivo deste trabalho foi propor um método de cozimento das mortadelas elaboradas com carne suína e com carne de frango com tempo reduzido pelo aumento da temperatura no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 10 publications
0
5
0
1
Order By: Relevance
“…Similar results were found by Jorge et al (), who observed 6.10–6.68 pH values for mortadella (chicken, pork, and beef meat). Orsolin et al (), in the study for cooking time reduction in chicken mortadella production, found pH values around 6.41, and during the storage time, a pH value decrease was observed (around 6.35). In addition, similar results were also found by Yunes et al (), Trindade et al () and Viuda‐Martos et al (), who reported pH values from 6.2 to 6.33 and decreased value during storage time to 5.7–5.81.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…Similar results were found by Jorge et al (), who observed 6.10–6.68 pH values for mortadella (chicken, pork, and beef meat). Orsolin et al (), in the study for cooking time reduction in chicken mortadella production, found pH values around 6.41, and during the storage time, a pH value decrease was observed (around 6.35). In addition, similar results were also found by Yunes et al (), Trindade et al () and Viuda‐Martos et al (), who reported pH values from 6.2 to 6.33 and decreased value during storage time to 5.7–5.81.…”
Section: Resultsmentioning
confidence: 97%
“…On the other hand, the pH of the mass had influenced the emulsion stability (Arslan, 2006 Similar results were found by Jorge et al (2015), who observed 6.10-6.68 pH values for mortadella (chicken, pork, and beef meat). Orsolin et al (2015), in the study for cooking time reduction in chicken mortadella production, found pH values around 6.41, and during the storage time, a pH value decrease was observed (around 6.35). In due to the action of lactic acid bacteria and the storage temperature that can produce acidification of the product, and, therefore, the decrease in pH occurs.…”
Section: Physical-chemical Analysismentioning
confidence: 89%
See 2 more Smart Citations
“…Embutidos secos crus passam por um processo de desidratação parcial, como o salame, que também é classificado como um produto fermentado (Vedovatto et al, 2019). A salsicha e a mortadela passam por um processo de emulsificação seguido de tratamento térmico (Orsolin et al, 2015). Existem também os produtos curados e maturados como o presunto suíno, nos quais são adicionados sais de cura e condimentos, com o objetivo de conservação e melhoria nas propriedades sensoriais.…”
Section: Resultsunclassified